Preliminary Long-Term Experimental Characterization of a Solid Oxide Fuel Cell Operated in DIR-SOFC Mode. (10th July 2019) - Kupecki, Jakub; Wierzbicki, Michal; Jagielski, Stanislaw; Kluczowski, Ryszard; Motylinski, Konrad; Skrzypkiewicz, Marek
Abstract : This article discusses the experimental characterization of a 50 mm x 50 mm anode supported solid oxide fuel cell with active area of 16 cm 2 which was operated in direct internal reforming conditions over an extended period of time. The cell with a given composition of electrodes and electrolyte (NiO-YSZ/YSZ/GDC/LSCF) was subject to complete internal reforming of methane for 1, 000 hours. Analysis of the performance included electrochemical characterization (j-V curves and EIS) and measurement of the composition of gases exiting the anodic compartments of the cell. This approach was used to observe the degradation of performance and to determine the effect of the state of the cell on the molar fraction of gases in the outlet. Microstructure studies provided insight into the changing structure of the electrodes after the degradation was observed. The results are quantified and discussed.